1995
DOI: 10.1677/jme.0.0140051
|View full text |Cite
|
Sign up to set email alerts
|

High-level expression of recombinant porcine LH receptor in baculovirus-infected insect cells or caterpillars

Abstract: Porcine LH receptor ectodomain was overexpressed in insect cells and lepidopteran larvae using the recombinant baculovirus expression system. A low multiplicity of infection yielded the largest active production, of approximately 10(7) receptors/cell or 3 micrograms active receptor/mg total protein in infected cells. The truncated ectodomain solubilized with Triton X-100 bound its ligand with a high affinity which was comparable with that of the native membrane receptor. Increasing the multiplicity of infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Previous reports suggested that a portion of recombinant membrane proteins, including G-coupled receptors, produced in Sf9 cells does not reach the cell surface but remains in the endoplasmic reticulum and Golgi compartments because of possible saturation of the translocation machinery of the insect cell (22)(23)(24)(25). This hypothesis is also supported by our immunofluorescence experiments on permeabilized Sf9 cells expressing hMOR-his in which antibody labeling was detected not only at the cell surface but also inside the cell.…”
Section: Effect Of the Amino-terminal Histidine Tag On Receptor Expresupporting
confidence: 87%
“…Previous reports suggested that a portion of recombinant membrane proteins, including G-coupled receptors, produced in Sf9 cells does not reach the cell surface but remains in the endoplasmic reticulum and Golgi compartments because of possible saturation of the translocation machinery of the insect cell (22)(23)(24)(25). This hypothesis is also supported by our immunofluorescence experiments on permeabilized Sf9 cells expressing hMOR-his in which antibody labeling was detected not only at the cell surface but also inside the cell.…”
Section: Effect Of the Amino-terminal Histidine Tag On Receptor Expresupporting
confidence: 87%
“…For example, two receptors were expressed with femtomolar expression levels in the Archea Halobacterium salinarum, the b 2 -adrenergic receptor [101] and the yeast a-mating factor receptor [100]. A caterpillar expression system was used to express, in a nonfunctional form, the extracellular part of the luteinizing hormone (LH) receptor, a member of the glycoprotein hormone family [102]. Heterologous expression in Xenopus oocytes was realised, but this system was mainly used to study GPCR functional coupling since protein expression requires mRNA injection into each oocyte, which prevents large-scale production [103].…”
Section: Other Systemsmentioning
confidence: 99%
“…A number of different glycoprotein hormone genes have been expressed in mammalian cell lines in recombinant forms, including in a non-exhaustive list, human CGß (Bedows et al 1991), bovine (b) a-subunit (Campbell et al 1992) and bLHß (Kaetzel et al 1989). The baculovirus expression system, utilizing the Autographa californica multiple nuclear polyhedrosis virus (AcMNPV) and Spodoptera frugiperda (Sf9) cells, has shown great potential in the synthesis of a variety of proteins (Vlak et al 1992) such as different glycoprotein hormone subunits (Huang et al 1991, Nakhai et al 1991, Jha et al 1992, Sridhar & Hasnain 1993 and glycoprotein hormone receptors (Christophe et al 1993, Misrahi et al 1994, Pajot-Augy et al 1995. This system is known to correctly process and post-translationally modify the proteins expressed (O'Reilly et al 1992).…”
Section: Introductionmentioning
confidence: 99%